FROM FOMO TO HODL: AN ANALYSIS OF JARGON IN CRYPTOCURRENCY YOUTUBE VIDEOS - Mirza Muhammad Abu Fadhl Abbas; Evi Jovita Putri (IdeBahasa, 2026)
Using Yule’s paradigm of word formation and jargon functions, this study investigated the formation and purposes of jargon in Bitcoin and cryptocurrency conversation. It sought to clarify the linguistic construction of specialized language and its social functions in digital financial communication. Data were gathered from two YouTube-based bitcoin content sources using a qualitative descriptive method. Jargon phrases were identified, categorized, and semantically interpreted. The results demonstrated that an organized jargon system incorporating both technical and social characteristics is used in cryptocurrency debate. The most common word-formation technique is compounding, which is followed by derivation and borrowing. Conversion, blending, and acronymy/initialism are less common. Functionally, jargon fulfills three main roles: efficiency, exclusion, and in-group identity. Compounding and conversion enhance communicative efficiency, derivation and borrowing restrict accessibility, and blending and acronymy signal community membership. Furthermore, this research indicated that the most frequent formation types particularly compounding and derivation are intimately linked to the dominating functions of efficiency and exclusion. Overall, cryptocurrency jargon functioned as a strategic linguistic system shaping expert communication and social identity.